2019
DOI: 10.1007/s11947-019-2238-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Thermal Behaviours of Heat-Moisture-Treated Starch-Rich Wheat-Based Blended Matrices: Impact of Treatment of Non-wheat Flours

Abstract: The significance of heat moisture treatment (HMT, 15% moisture content, 1 h and 120ºC) of single common wheat (WT), teff (T), chestnut (CN) and whole chickpea (CP) flours has been investigated a) on main chemical, nutritional and functional flour parameters and b) on visco-metric and thermal behaviors of treated blended breads. Characterization of native and HMT flours evidenced significant (p<0.05) but discreet effects of the thermal treatment of flours on main functional parameters in terms of promotion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Eliasson et al [57] observed that the physical and chemical properties of starches were radically altered after MHT [52,59]. Enhanced RS contents and reduced enzyme vulnerability of starches may be accomplished by different time/temperature treatments; this has been shown previously for starches of different botanical origin and with varying amylose/amylopectin ratios [48,60,61,62,63,64,65,66,67,68]. Dehydrated heating (130 °C) of waxy corn starch expanded the GDS content.…”
Section: Microstructure Of Rice Grainsmentioning
confidence: 84%
“…Eliasson et al [57] observed that the physical and chemical properties of starches were radically altered after MHT [52,59]. Enhanced RS contents and reduced enzyme vulnerability of starches may be accomplished by different time/temperature treatments; this has been shown previously for starches of different botanical origin and with varying amylose/amylopectin ratios [48,60,61,62,63,64,65,66,67,68]. Dehydrated heating (130 °C) of waxy corn starch expanded the GDS content.…”
Section: Microstructure Of Rice Grainsmentioning
confidence: 84%
“…The nutritional and technological behavior of wheat flour can be changed by applying various physical treatments, one of them being heat-moisture treatment (HMT) which implies flour heating at higher level than the gelatinization temperature and under water restriction (<35%) [2]. HMT is an easy to control process and it is eco-friendly compared to chemical modifications of starch-based matrices.…”
Section: Introductionmentioning
confidence: 99%